1991
DOI: 10.1152/ajplung.1991.261.6.l472
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of surfactant by alveolar macrophages in vitro

Abstract: Because of their localization and function as phagocytes, alveolar macrophages could take part in the catabolism of surfactant, including surfactants used for treatment. Conditions of the ingestion of the surfactant preparation AWD 56-02 by alveolar macrophages in vitro are described in this paper. The surfactant was labeled with rhodaminyl phosphatidylethanolamine and incubated with alveolar macrophages lavaged from rat lungs. Membrane binding and phagocytosis were evaluated by fluorescence microscopy and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…The activity of this enzyme is regulated by various effector molecules (26,27). The lower content of phospholipid in extracellular surfactant may be a consequence of greater uptake by macrophages or increased recycling by neumocytes type II for synthesis of new surfactant (28,29). In our experiment we observed an increased phospholipid concentration in alveolar macrophages of Ca compared to Co.…”
Section: Discussionsupporting
confidence: 49%
“…The activity of this enzyme is regulated by various effector molecules (26,27). The lower content of phospholipid in extracellular surfactant may be a consequence of greater uptake by macrophages or increased recycling by neumocytes type II for synthesis of new surfactant (28,29). In our experiment we observed an increased phospholipid concentration in alveolar macrophages of Ca compared to Co.…”
Section: Discussionsupporting
confidence: 49%
“…No effects were observed for fibronectin, vitronectin, and hemoglobin (Table 3). Bilirubin, usually found at low concentrations in (4) 0.00 f 0.31 (3) 1.85 f 0.45 (4) 0.41 f 0.12 (4) 1.47 f 0.23 (10) 2.07 f 0.29 (8) 2.17 f 0.39 (8) 2.42 * 0.49 (7) 2.36 r 1.16 (3) 0.82 f 0.2 (6) 0.37 f 0.11 (6) 0.27 f 0.18 (6) 3.54 f 1.30 (5) 3.11 f 1.20 (5) 3.58 f 1.80 (5) 1.05 f 0.24 (5) 1.06 f 0.26 (5) 1.47 f 0.43 (5) 0.67 f 0.16 (10) 0.72 f 0.13 (10) 0.43 f 0.19 (10) 0.62 f 0.34 (10) 3 Data are means f SE from n experiments as indicated in parentheses. Cells were isolated from lungs of adult rats, cultured for 18 h. After the preincubation of the cells in a fresh medium for 30 min, a [3H]DPPGlabeled, lipid-extracted, natural surfactant (50 pM) was added, followed by the addition of the serum component or its solvent.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro uptake of liposomes by macrophages is enhanced by IgG [ 181, fibronectin [ 181, vitronectin [22], and whole serum, respectively, heat-labile components [6]. This effect on surfactant liposomal uptake by alveolar macrophages has been proposed as one of the potential mechanisms for an increased contribution of macrophages in the clearing of alveolar surfactant under pathological conditions [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, Mtb in vivo could utilize surfactant lipids as a nutrient source not only within the alveolar lumen, but also following Mtb phagocytosis by macrophages. It has previously been shown that alveolar macrophages internalize surfactant lipids [32,33,34], which would thus be potentially accessible for metabolic use by intracellular Mtb. Although Mtb bacilli have their own internal lipid stores, the opportunistic use of surfactant lipids for metabolism would reduce the need for de novo synthesis by these organisms.…”
Section: Discussionmentioning
confidence: 99%